Pengunaan Bahasa Indonesia Yang Baik dan Benar Dalam Menggunakan Media Sosial - Widya Herliana Dewi Rambe; Rea Brema Br Sipayung; Mita Oktaviani Simanjuntak; M. Surip (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Human life cannot be separated from language. Every day, even at all times, humans use language to communicate to convey goals, ideas, thoughts and even desires. In communication, it is very important to use good and correct language, whether communicating implicitly or explicitly. In the digital era, indirect communication can be done using social media, which is almost the same as written communication, but many people use non-standard language, slang, abbreviations that are not in accordance with the KBBI, and many sentences have even changed meaning. This research uses a literature study method by searching and collecting data from various references. This article aims to pay attention to the language used to avoid communication that is not good enough to not reflect the friendly, polite, polite and civilized character of Indonesian. From the data collected, many social media users use language that is not good and correct in expressing feelings, thoughts and responses to other social media users.